THE USE OF MIND MAPPING TECHNIQUES IN TEACHING WRITING ON EXPOSITION GENRE - Kartinah, Atin (2013)
This study investigated the use of mind mapping techniques in teaching writing. It examined (1) the effect of mind mapping techniques on students' ability in writing exposition genre and (2) the students' opinion on the use of the techniques. Mixed method was employed in this study. The participants included 60 eighth-grade students of a junior high school in Garut: 30 students became the experimental group and the other 30 became the control group. This study examined two types of data. The first data were texts written by both the experimental and control groups in both the pre-test and post-test. The texts were scored, to be compared through inferential statistics (u-test and t-test). The second data were the students' opinion, which was gathered through an interview. This study found that the starting ability of both the experimental and control groups was equal. At the end of the treatment the ability of both groups was found to be significantly different. Since the experimental group's scores were higher, it can be concluded that the treatment (mind mapping) affected the students' ability in writing exposition texts. It is also found this effectiveness is supported by the findings from the interview: the students found the learning activities both enjoyable and beneficial. Key word: Mind mapping technique, Teaching writing,Exposition genre